Method for preparing high-toughness titanium-based composite material through solid-phase reaction sintering
Through the "titanium thermal reaction" of CuO and Ti during solid phase sintering and multi-pass variable speed rolling deformation process, titanium-based composite materials with high strength and toughness and uniform reinforcement body distribution were prepared, solving the energy consumption problems caused by uneven dispersion of reinforcement bodies and high-temperature sintering in the prior art.
Patent Information
- Application Number
- CN202411582975.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-28
AI Technical Summary
In titanium-based composite materials, direct application of multi-scale reinforcement bodies is easy to introduce contaminated elements, resulting in poor interface bonding, and it is difficult to achieve uniform dispersion of reinforcement bodies, hindering the improvement of the mechanical properties of composite materials. In addition, existing titanium-based composite materials reinforced with in-situ self-generating ceramic particles require a higher sintering temperature, resulting in high energy consumption.
The "titanium thermal reaction" occurs during solid phase sintering by CuO and Ti, and the nano-Ti euthanized phase is uniformly distributed in the grain boundaries and crystals through a multi-pass variable speed rolling deformation process, reducing the sintering temperature and realizing the preparation of high-strength tough titanium-based composite materials.
Through the integrated method of solid phase reaction sintering and hot rolling deformation, the high-strength tough titanium-based composite material prepared has multiple distribution methods of nanoeutectic phases, which significantly improves the comprehensive mechanical properties of the composite material and reduces processing energy consumption.
Smart Images

Figure CN119530588A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a high-strength and tough titanium-based composite material by solid-phase reaction sintering, and belongs to the technical field of titanium-based composite material preparation. Background Art
[0002] Titanium Matrix Composites (TMCs) have the advantages of high specific strength, low density, and corrosion resistance, and are widely used in the aerospace and weapons industries. However, directly adding multi-scale reinforcements to TMCs can easily introduce contamination elements, resulting in poor interface bonding, and it is difficult to achieve uniform dispersion of reinforcements by the addition method, which hinders the improvement of the mechanical properties of the composites. On the other hand, the in-situ self-generated ceramic particle reinforced (titanium boride, titanium carbide) titanium-based composites that are currently widely studied often require higher sintering temperatures (>1200°C) to achieve sufficient in-situ reactions. This high-temperature processing method usually results in huge energy consumption. Therefore, obtaining uniformly distributed reinforcements, preparing high-strength and tough TMCs, and reducing processing energy consumption are difficult problems that need to be solved urgently in the face of titanium-based composites.
[0003] Researchers have found that copper oxide and titanium can undergo a high-temperature self-propagating reaction ("titanium thermal reaction") similar to the "aluminum thermite reaction" during the solid-phase sintering process. Compared with other titanium-based composite materials prepared by in situ reactions, solid-phase reaction sintering releases a large amount of heat and has a faster reaction rate. Based on the high-temperature self-propagating reaction characteristics of copper oxide and titanium, the solid-phase sintering method can reduce the sintering temperature to achieve the effect of reducing processing energy consumption. Compared with the many defects of the direct addition method, the solid-phase sintering method can effectively reduce the impurities introduced into the CuO / Ti composite material, minimize the segregation of the sintered components, eliminate rough and uneven structures, reduce the sintering temperature, and obtain a uniformly distributed reinforcement. However, there are few reports on the preparation of high-strength and toughness titanium-based composite materials by solid-phase sintering reaction method, and the organization and performance indicators of the composite materials prepared by the new method remain to be explored. Summary of the Invention
[0004] To address the challenges of preparing high-strength and toughness titanium-based composites and reducing processing energy consumption, this invention utilizes a "titanium-heat reaction" between CuO and Ti during solid-phase sintering. This reaction is intense and releases a large amount of heat, promoting the reaction and element diffusion, enabling sintering at lower temperatures. Combined with multi-pass variable-speed rolling deformation, the composite undergoes multiple eutectoid transformation reactions. The resulting nano-Ti2Cu eutectoid phase has a variety of distribution patterns, both distributed at grain boundaries with a unique micro-network structure and evenly distributed within the grains, resulting in a high-strength and toughness titanium-based composite with excellent overall performance.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A method for preparing a high-strength and tough titanium-based composite material by solid-phase reaction sintering comprises the following steps:
[0007] (1) Preparation of nano-copper oxide
[0008] Copper acetate (Cu(CH3COO)2·H2O) and sodium hydroxide (NaOH) were dissolved in deionized water, and sodium hydroxide was added dropwise to the copper acetate. The mixed solution was subjected to magnetic stirring, heating, washing, suction filtration, and drying to prepare nano-copper oxide (CuO).
[0009] Further optimization, the specific steps of preparing nano copper oxide in step (1) are as follows: (Cu(CH3COO)2·H2O) and NaOH are dissolved in deionized water respectively and ultrasonically dispersed evenly, and then NaOH solution is added dropwise to the (Cu(CH3COO)2·H2O) suspension until the suspension produces a large amount of dark blue precipitate, and the obtained suspension is heated and stirred in a 70-80°C magnetic stirring water bath until the suspension completely turns black, and then kept warm and magnetically stirred for 30 minutes. After the reaction is completed, the suspension is washed with deionized water solution to be colorless and neutral, and then the suspension is vacuum filtered. Finally, the obtained CuO is placed in a vacuum condition at 60-70°C and dried for 4-6 hours to obtain the prepared black powder nano CuO.
[0010] Furthermore, the molar ratio of copper acetate to sodium hydroxide is 3:5, and the concentration of copper acetate in the aqueous solution is 3-15 mg / mL.
[0011] (2) Preparation of CuO / Ti-based composite powder
[0012] CuO is uniformly dispersed in an ethanol solution by ultrasonication to obtain a CuO suspension, and then titanium matrix powder is added to the CuO suspension, stirred and mixed uniformly, ball milled, and dried by rotary evaporation to obtain a CuO / Ti-based composite powder;
[0013] Furthermore, the CuO mixed suspension added with the Ti matrix powder is stirred by electromagnetic stirring at a stirring rate of 200-800 r / min for 10-20 min and a frequency of 10-60 KHz.
[0014] Furthermore, the drying process is performed using a vacuum rotary evaporator to remove the alcohol solvent to obtain a powder mixture; wherein the rotary evaporation flask is placed in a constant temperature water bath at a temperature of 30-60°C for 1-2 hours, and the flask rotates at a speed of 10-100 r / min.
[0015] (3) Solid phase sintering
[0016] The CuO / Ti composite powder is sintered: the dried CuO / Ti composite powder is molded into a cylindrical compact, and the compact is moved into a rapid hot pressing sintering furnace for sintering to obtain a consolidated sintered green body;
[0017] Furthermore, the specific steps of pressing the green body are: loading the CuO / Ti composite powder into a graphite mold, placing the graphite mold containing the powder mixture into a hydraulic press, setting a pre-pressure of 0-20 MPa, and maintaining the pressure for 0-60 minutes; and completing the pressing and forming of the powder mixture.
[0018] Furthermore, the specific steps of sintering are: placing the pressed green sheet into a rapid hot pressing sintering furnace, and the preset sintering program is that the initial vacuum degree is ≤5Pa, the initial heating rate is set to 10-50℃ / min, when the temperature rises to 300-500℃, the heating rate is adjusted to 50-100℃ / min, and when the temperature rises to 600-950℃, it is kept warm for 5-20min, and then cooled with the furnace to complete the rapid hot pressing sintering of the green sheet to obtain a dense green body.
[0019] (4) Thermal deformation during variable speed rolling
[0020] The sintered green body is thermally deformed by a multi-pass variable speed rolling process. That is, the sintered green body is first thermally deformed by a low temperature and low speed rolling process, and then the pre-deformed green body is thermally deformed by a high temperature and high speed rolling process. By adjusting the thermal deformation parameters, the different distribution states of nano-Ti2Cu and titanium matrix in the matrix are controlled, and finally the grain boundary micronetwork structure and intracrystalline distribution of nano-Ti2Cu in the reinforcement are realized, thereby synergistically strengthening the titanium-based composite material.
[0021] Furthermore, low-speed rolling is carried out according to the following steps: the starting rolling temperature is 800-1000°C, the circumferential speeds of the upper and lower rolls are controlled to be equal, and the rotation speed is 100-600r / s; the deformation amount of each pass is 3-40%, and the total deformation amount is 10-80%; the re-melting temperature between passes is 800-1000°C, and the re-melting holding time between passes is 2-8min.
[0022] Furthermore, high-speed rolling is performed according to the following steps: the starting rolling temperature is 800-1000°C; the rotation speed is 500-1000r / s; the deformation of each pass is 3-40%, and the total deformation is 10-80%; the re-melting temperature between passes is 800-1000°C, and the re-melting holding time between passes is 2-8min. By regulating the hot rolling process conditions, Ti2Cu is arranged in a micro-network at the grain boundaries during the process, and the nano-eutectoid phase is uniformly distributed within the grain. Finally, a titanium-based composite material reinforced by the coupling of Ti2Cu with a micro-network distribution at the grain boundaries and nano-Ti2Cu within the grains is prepared.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The zero-dimensional nano-needle oxide (CuO) used in the present invention is evenly dispersed in the titanium matrix by ball milling. During the solid-phase sintering reaction, CuO and titanium undergo a "titanium thermal reaction". Compared with traditional sintering reactions, the reaction speed is faster, the sintering time is shorter, and the sintering temperature is lower.
[0025] (2) The present invention uses a method of integrating solid-phase sintering reaction and hot rolling deformation to prepare a high-strength and tough titanium-based composite material. The nano-eutectoid phase has multiple distribution modes: it is distributed in a unique micro-network at the grain boundary and is evenly distributed within the crystal, thereby obtaining a high-strength and tough titanium-based composite material.
[0026] (3) The present invention prepares reinforcements with various distribution patterns to synergistically reinforce titanium-based composite materials. From the perspective of the reinforcement mechanism, the micro-network precipitated phase distributed at the grain boundaries inhibits the migration of the matrix grain boundaries during deformation, while the nano-Ti2Cu eutectic phase within the grains improves the storage capacity of dislocations, thereby synergistically improving the comprehensive mechanical properties of the composite material.
[0027] (4) The method of the present invention is simple to operate, highly practical, and highly universal, and provides guidance for the research and development of advanced high-strength and high-toughness titanium-based composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the SEM (scanning electron microscope) image of the nano-CuO prepared in step (1) of Example 1.
[0029] Figure 2 This is the SEM (scanning electron microscope) image of the composite powder prepared in step (2) of Example 1.
[0030] Figure 3 This is a SEM (scanning electron microscope) image of the sintered block of the composite material prepared in step (4) of Example 1.
[0031] Figure 4 TEM of the CuO / Ti composite material in step (4) of Example 1 Figure 1 .
[0032] Figure 5 TEM of the CuO / Ti composite material in step (4) of Example 1 Figure 2 .
[0033] Figure 6 Graph showing the tensile properties of the composite materials prepared in Example 1 and Comparative Example 1.
[0034] Figure 7 Graph showing the tensile properties of the composite materials prepared in Example 2 and Comparative Example 2.
[0035] Figure 8Graph showing the tensile properties of the composite materials prepared in Example 3 and Comparative Example 3.
[0036] Figure 9 Graph showing the tensile properties of the composite materials prepared in Example 4 and Comparative Example 4. DETAILED DESCRIPTION
[0037] The present invention is further described below with reference to the accompanying drawings and specific embodiments. The methods described are conventional methods unless otherwise specified, and the raw materials described can be obtained from public commercial channels unless otherwise specified.
[0038] Copper acetate (Cu(CH3COO)2·H2O), 95%); sodium hydroxide (NaOH, 99.9%), Shanghai Aladdin Reagent Co., Ltd.
[0039] Ti and TC4 matrix powders are spherical, with a particle size of 0-45 μm and a purity of 99.9 wt.%, from Ganzhou Jingke Technology Co., Ltd.
[0040] Example 1
[0041] A method for preparing high-strength and toughness titanium-based composite materials by solid-phase reaction sintering, the specific steps are as follows:
[0042] (1) Preparation of copper oxide
[0043] 1.1) Dissolve 15.6 g of copper acetate (Cu(CH3COO)2·H2O) and 7 g of sodium hydroxide (NaOH) in 500 mL and 30 mL of deionized water, respectively. Ultrasonic dispersion was performed for 10 min to obtain a blue suspension and a transparent solution. The sodium hydroxide solution was then added dropwise to the blue suspension. The mixture was heated in a magnetically stirred water bath at 80°C for 30 min to obtain a CuO suspension.
[0044] 1.2) Wash with deionized water until the filtrate is colorless and neutral, vacuum filter the CuO suspension, and place the resulting CuO black powder in a vacuum drying oven at 60°C for 6 hours to obtain the prepared black powdered CuO. The microscopic morphology of CuO is as follows: Figure 1 As shown, it is needle-like and feathery;
[0045] (2) Preparation of CuO / Ti-based composite powder
[0046] 2.1) Weigh 0.3 g of CuO solid powder and add it to 100 mL of ethanol solution. Ultrasonic dispersion is performed for 10 min to ensure uniform dispersion of the CuO.
[0047] 2.2) 14.70 g of pure Ti powder was added to the uniformly dispersed CuO suspension. The mixed suspension was electromagnetically stirred at a rate of 350 r / min and a frequency of 20 kHz for 10 min, ball-milled for 240 min, and then dried using a vacuum rotary evaporator. The rotary evaporator was placed in a constant temperature water bath at a temperature of 50°C for 2 h and rotary dried at a rotation speed of 100 r / min to obtain a CuO / Ti composite powder. The micromorphology of the composite powder is characterized as follows: Figure 2 As shown in the figure, the titanium substrate is ground into flakes under the action of ball milling, which increases the specific surface area, and copper oxide is evenly dispersed on the surface of the titanium substrate without agglomeration.
[0048] (3) Rapid hot pressing sintering
[0049] 3.1) 15 g of CuO / Ti composite powder was placed into a 20 mm Φ cylindrical graphite mold. The mold was then placed in a hydraulic press with a preload of 5 MPa and maintained for 2 min. The powder mixture was then compacted.
[0050] 3.2) The compacted green body was placed in a rapid hot pressing furnace with an initial vacuum of ≤5 Pa and an initial heating rate of 50°C / min. When the temperature reached 400°C, the heating rate was adjusted to 100°C / min. When the temperature reached 650°C, it was held for 5 minutes and then cooled in the furnace to complete the rapid hot pressing sintering of the green body. A sintered CuO / Ti green body was obtained.
[0051] (4) Thermal deformation during variable speed rolling
[0052] 4.1) The CuO / Ti sintered body was first subjected to thermal deformation treatment using a low-speed rolling process. The starting rolling temperature was 850°C, and the circumferential speed of the upper and lower rollers was controlled to be equal and the rotation speed was 400 r / min. The deformation amount per pass was 15%, and the total deformation amount was 30%. The re-melting temperature between passes was 850°C, and the re-melting holding time between passes was 2 min.
[0053] 4.2) Then, high-speed rolling is used to perform hot deformation treatment on the pre-deformed billet, with the starting rolling temperature of 850°C; the peripheral speed of the high-speed roller is 800r / min; the deformation amount of each pass is 25%, and the total deformation amount is 50%; the re-melting temperature between passes is 850°C, and the re-melting holding time between passes is 2min, to obtain the final processed sample. By regulating the hot rolling process, Ti2Cu can achieve grain boundary micro-network arrangement during the deformation process, and at the same time, the strong phase of Ti2Cu nano-precipitates can be evenly distributed within the crystal. The composite material is characterized by SEM as follows Figure 3 As shown, nano-precipitated Ti2Cu was obtained, and the composite material was characterized by TEM. Figure 4 、 Figure 5As shown in Figure 3, the Ti2Cu precipitated phase has a variety of distribution morphologies, presenting a unique micro-network distribution at the grain boundary and uniform distribution within the grain.
[0054] Comparative Example 1
[0055] A method for preparing high-strength and toughness titanium-based composite materials by solid-phase reaction sintering, the specific steps are as follows:
[0056] (1) Weigh 15 g of pure Ti powder and add it to 100 mL of ethanol solution. After electromagnetic stirring at a rate of 350 r / min and a frequency of 20 kHz for 10 min, ball mill for 240 min, and then dry it using a vacuum rotary evaporator. The rotary evaporator is placed in a constant temperature water bath at a temperature of 50°C for 2 h and rotary evaporated at a rotation speed of 100 r / min to obtain the ball-milled titanium matrix powder.
[0057] (2) The powder after ball milling and drying in (1) is loaded into a Φ20mm cylindrical graphite mold, and the graphite mold is placed in a hydraulic press, the pre-pressure is set to 5MPa, and the pressure is maintained for 2min; then the powder mixture is pressed and formed; the pressed green compact is placed in a rapid hot pressing furnace, the initial vacuum degree is ≤5Pa, the initial heating rate is set to 50℃ / min, when the temperature rises to 400℃, the heating rate is adjusted to 100℃ / min, and when the temperature rises to 650℃, the temperature is maintained for 5min, and then cooled with the furnace to complete the rapid hot pressing sintering of the green compact to obtain a sintered pure titanium green body;
[0058] (3) First, the pure titanium sintered blank was subjected to thermal deformation treatment by low-temperature and low-speed rolling process, the starting rolling temperature was 850℃, the circumferential speed of the upper and lower rollers was controlled to be equal and the rotation speed was 400r / min; the deformation amount of each pass was 15%, and the total deformation amount was 30%; the furnace temperature between passes was 850℃, and the furnace holding time between passes was 2min; secondly, the pre-deformed blank was subjected to thermal deformation treatment by high-temperature and high-speed rolling process, the starting rolling temperature was 850℃; the circumferential speed of the high-speed roller was 800r / min; the deformation amount of each pass was 25%, and the total deformation amount was 50%; the furnace temperature between passes was 850℃, and the furnace holding time between passes was 2min, and the final processed sample was obtained.
[0059] The tensile properties of the materials prepared in Example 1 and Comparative Example 1 were tested. The results are as follows: Figure 6As shown in the figure; the yield strength (YS) of the composite material is 1100MPa, the ultimate tensile strength (UTS) is 1250MPa, and the elongation is 8.3%. Under the same preparation process, the yield strength is increased by 66% and the ultimate tensile strength is increased by 78% compared with pure titanium. The performance is significantly improved. This is due to the nano-eutectoid phase Ti2Cu generated by the "titanium thermal reaction" between copper oxide and titanium. The micro-network precipitate phase distributed at the grain boundary inhibits the migration of the matrix grain boundary during deformation. At the same time, the intracrystalline nano-Ti2Cu eutectoid phase improves the storage capacity of dislocations, synergistically improving the comprehensive mechanical properties of the composite material.
[0060] Example 2
[0061] A method for preparing high-strength and toughness titanium-based composite materials by solid-phase reaction sintering, the specific steps are as follows:
[0062] (1) Preparation of copper oxide
[0063] 1.1) Dissolve 15.6 g of copper acetate (Cu(CH3COO)2·H2O) and 7 g of sodium hydroxide (NaOH) in 500 mL and 30 mL of deionized water, respectively. Ultrasonic dispersion was performed for 10 min to obtain a blue suspension and a transparent solution. The sodium hydroxide solution was then added dropwise to the blue suspension. The mixture was heated in a magnetically stirred water bath at 80°C for 30 min to obtain a CuO suspension.
[0064] 1.2) Washing with deionized water until the filtrate is colorless and neutral, vacuum filtering the CuO suspension, and drying the resulting black CuO powder in a vacuum drying oven at 60°C for 6 h to obtain the prepared black powdered CuO in the form of needles and feathers;
[0065] (2) Preparation of CuO / Ti-based composite powder
[0066] 2.1) Weigh 0.3 g of CuO solid powder and add it to 100 mL of ethanol solution. Ultrasonic dispersion is performed for 10 min to ensure uniform dispersion of the CuO.
[0067] 2.2) 14.70 g of pure Ti powder was added to the uniformly dispersed CuO suspension. The mixed suspension was electromagnetically stirred at 350 rpm and 20 kHz for 10 min, ball-milled for 240 min, and then dried using a vacuum rotary evaporator. The rotary evaporator was placed in a constant temperature water bath at 50°C for 2 h and rotary-dried at 100 rpm to obtain a CuO / Ti composite powder. The titanium substrate was ground into flakes by ball milling, increasing the specific surface area. The copper oxide was uniformly dispersed on the surface of the titanium substrate without agglomeration.
[0068] (3) Rapid hot pressing sintering
[0069] 3.1) 15 g of CuO / Ti composite powder was placed into a 20 mm Φ cylindrical graphite mold. The mold was then placed in a hydraulic press with a preload of 5 MPa and maintained for 2 min. The powder mixture was then compacted.
[0070] 3.2) The compacted green body was placed in a rapid hot pressing furnace with an initial vacuum of ≤5 Pa and an initial heating rate of 50°C / min. When the temperature reached 400°C, the heating rate was adjusted to 100°C / min. When the temperature reached 950°C, the green body was held at that temperature for 5 minutes and then cooled in the furnace to complete the rapid hot pressing sintering of the green body. A sintered CuO / Ti green body was obtained.
[0071] (4) Rolling thermal deformation
[0072] The pre-deformed billet was subjected to thermal deformation treatment by high-temperature and high-speed rolling, with the starting rolling temperature being 950°C; the peripheral speed of the high-speed roller being 700 r / min; the deformation amount per pass being 25%, and the total deformation amount being 75%; the re-melting temperature between passes being 950°C, and the re-melting holding time between passes being 2 min, to obtain the final processed sample.
[0073] Comparative Example 2
[0074] A method for preparing high-strength and toughness titanium-based composite materials by solid-phase reaction sintering, the specific steps are as follows:
[0075] (1) Weigh 15 g of pure Ti powder and add it to 100 mL of ethanol solution. After electromagnetic stirring at a rate of 350 r / min and a frequency of 20 kHz for 10 min, ball mill for 240 min, and then dry it using a vacuum rotary evaporator. The rotary evaporator is placed in a constant temperature water bath at a temperature of 50°C for 2 h and rotary evaporated at a rotation speed of 100 r / min to obtain the ball-milled titanium matrix powder.
[0076] (2) The powder after ball milling and drying in (1) is loaded into a Φ20mm cylindrical graphite mold, and the graphite mold is placed in a hydraulic press, the pre-pressure is set to 5MPa, and the pressure is maintained for 2min; then the powder mixture is pressed and formed; the pressed green compact is placed in a rapid hot pressing furnace, the initial vacuum degree is ≤5Pa, the initial heating rate is set to 50℃ / min, when the temperature rises to 400℃, the heating rate is adjusted to 100℃ / min, and when the temperature rises to 850℃, the temperature is maintained for 20min, and then cooled with the furnace to complete the rapid hot pressing sintering of the green compact to obtain a sintered pure titanium green body;
[0077] (3) The pre-deformed blank is subjected to thermal deformation treatment by high-temperature and high-speed rolling, with the starting rolling temperature being 950°C; the peripheral speed of the high-speed roller being 700 r / min; the deformation amount per pass being 25%, and the total deformation amount being 75%; the re-melting temperature between passes being 950°C, and the re-melting holding time between passes being 2 min, to obtain the final processed sample.
[0078] The tensile properties of the materials prepared in Example 2 and Comparative Example 2 were tested, and the results were as follows: Figure 7 As shown;
[0079] The strength and ductility of both the composite material and pure titanium decreased compared to Example 1. This is primarily due to the altered sintering temperature of the composite material. Sintering at high temperatures for extended periods of time resulted in grain coarsening and the precipitation of a large amount of eutectoid phase at grain boundaries, which compromised both strength and ductility. Furthermore, the use of high-temperature, high-speed, and low-pass rolling failed to achieve the desired effect of multiple passes in regulating the distribution of the eutectoid phase.
[0080] Example 3
[0081] A method for preparing high-strength and toughness titanium-based composite materials by solid-phase reaction sintering, the specific steps are as follows:
[0082] (1) Preparation of copper oxide
[0083] 1.1) Dissolve 15.6 g of copper acetate (Cu(CH3COO)2·H2O) and 7 g of sodium hydroxide (NaOH) in 500 mL and 30 mL of deionized water, respectively. Ultrasonic dispersion was performed for 10 min to obtain a blue suspension and a transparent solution. The sodium hydroxide solution was then added dropwise to the blue suspension. The mixture was heated in a magnetically stirred water bath at 80°C for 30 min to obtain a CuO suspension.
[0084] 1.2) Washing with deionized water until the filtrate is colorless and neutral, vacuum filtering the CuO suspension, and drying the resulting black CuO powder in a vacuum drying oven at 60°C for 6 h to obtain the prepared black powdered CuO in the form of needles and feathers;
[0085] (2) Preparation of CuO / TC4-based composite powder
[0086] 2.1) Weigh 0.45 g of CuO solid powder and add it to 100 mL of ethanol solution. Ultrasonicate and disperse for 15 min to ensure uniform dispersion of the CuO.
[0087] 2.2) 14.65 g of TiC₄ powder was added to the uniformly dispersed CuO suspension. The mixed suspension was electromagnetically stirred at 800 rpm and 60 kHz for 15 min, ball-milled for 240 min, and then dried using a vacuum rotary evaporator. The rotary evaporator was placed in a constant temperature water bath at 60°C for 1 h and then dried at 50 rpm to obtain a CuO / TiC₄ composite powder.
[0088] (3) Rapid hot pressing sintering
[0089] 3.1) 15 g of CuO / TC4 composite powder was placed into a 20 mm Φ cylindrical graphite mold. The mold was then placed in a hydraulic press with a preload of 10 MPa and maintained for 4 minutes. The powder mixture was then compacted.
[0090] 3.2) The compacted green body was placed in a rapid hot pressing furnace with an initial vacuum of ≤5 Pa and an initial heating rate of 50°C / min. When the temperature reached 500°C, the heating rate was adjusted to 100°C / min. When the temperature reached 850°C, the green body was held for 5 minutes and then cooled in the furnace to complete the rapid hot pressing sintering of the green body. A sintered CuO / TC4 green body was obtained.
[0091] (4) Thermal deformation during variable speed rolling
[0092] 4.1) The CuO / TC4 sintered body was first subjected to thermal deformation treatment using a low-speed rolling process. The starting rolling temperature was 1000°C, and the circumferential speed of the upper and lower rollers was controlled to be equal at 600 r / min. The deformation amount per pass was 40%, and the total deformation amount was 80%. The re-melting temperature between passes was 1000°C, and the re-melting holding time between passes was 3 min.
[0093] 4.2) The pre-deformed blank was then subjected to thermal deformation treatment by high-speed rolling, with an initial rolling temperature of 1000°C and a peripheral speed of 1000 r / min. The deformation amount per pass was 40%, and the total deformation amount was 80%. The inter-pass re-melting temperature was 1000°C, and the inter-pass re-melting holding time was 3 min, to obtain the final processed sample.
[0094] Comparative Example 3
[0095] A method for preparing high-strength and toughness titanium-based composite materials by solid-phase reaction sintering, the specific steps are as follows:
[0096] (1) Weigh 15 g of pure TC4 and add it to 100 mL of ethanol solution. After electromagnetic stirring at a rate of 800 r / min and a frequency of 60 kHz for 15 min, ball mill for 240 min, and then dry it using a vacuum rotary evaporator. The rotary evaporation bottle is placed in a constant temperature water bath at a temperature of 60°C for 2 h and rotary evaporated at a rotation speed of 50 r / min to obtain the ball-milled titanium matrix powder.
[0097] (2) The powder after ball milling and drying in (1) is loaded into a Φ20mm cylindrical graphite mold, and the graphite mold is then placed in a hydraulic press, with a pre-pressure of 10MPa and pressure maintained for 4min; then the powder mixture is pressed and formed; the pressed green compact is placed in a rapid hot pressing furnace, with an initial vacuum degree of ≤5Pa and an initial heating rate of 50°C / min. When the temperature rises to 500°C, the heating rate is adjusted to 100°C / min, and when the temperature rises to 850°C, the temperature is maintained for 5min, and then cooled with the furnace to complete the rapid hot pressing sintering of the green compact to obtain a sintered TC4 green body;
[0098] (3) First, the pure titanium sintered blank is subjected to thermal deformation treatment by low-temperature and low-speed rolling process, the starting rolling temperature is 1000℃, the circumferential speed of the upper and lower rollers is controlled to be equal and the rotation speed is 600r / min; the deformation amount of each pass is 40%, and the total deformation amount is 80%; the furnace temperature between passes is 1000℃, and the furnace holding time between passes is 3min; secondly, the pre-deformed blank is subjected to thermal deformation treatment by high-speed rolling, the starting rolling temperature is 1000℃; the circumferential speed of the high-speed roller is 1000r / min; the deformation amount of each pass is 40%, and the total deformation amount is 80%; the furnace temperature between passes is 1000℃, and the furnace holding time between passes is 3min, and the final processed sample is obtained.
[0099] The tensile properties of the materials prepared in Example 3 and Comparative Example 3 were tested. The results are as follows: Figure 8 As shown, the composite material has a yield strength (YS) of 1210 MPa, an ultimate tensile strength (UTS) of 1350 MPa, and an elongation of 8.1%. Compared to TC4, the yield strength is increased by 92% and the ultimate tensile strength is increased by 73% using the same preparation process. The solid-phase sintering reaction has significantly improved the material's performance. This is because solid-state sintering can effectively reduce impurities introduced into the composite material, minimize segregation of sintered parts, and eliminate rough and uneven microstructures. Solid-state sintering makes the reaction more controllable, which will facilitate the regulation of the microstructure to obtain the desired mechanical properties of the composite material. For different titanium matrices, the addition of copper oxide and the use of solid-phase sintering methods have played a significant strengthening role.
[0100] Example 4
[0101] A method for preparing high-strength and toughness titanium-based composite materials by solid-phase reaction sintering, the specific steps are as follows:
[0102] (1) Preparation of copper oxide
[0103] 1.1) Dissolve 15.6 g of copper acetate (Cu(CH3COO)2·H2O) and 7 g of sodium hydroxide (NaOH) in 500 mL and 30 mL of deionized water, respectively. Ultrasonic dispersion was performed for 10 min to obtain a blue suspension and a transparent solution. The sodium hydroxide solution was then added dropwise to the blue suspension. The mixture was heated in a magnetically stirred water bath at 70°C for 30 min to obtain a CuO suspension.
[0104] 1.2) Washing with deionized water until the filtrate is colorless and neutral, vacuum filtering the CuO suspension, and drying the resulting black CuO powder in a vacuum drying oven at 70°C for 4 hours to obtain the prepared black powdered CuO in the form of needles and feathers;
[0105] (2) Preparation of CuO / TC4-based composite powder
[0106] 2.1) Weigh 0.45 g of CuO solid powder and add it to 100 mL of ethanol solution. Ultrasonicate and disperse for 15 min to ensure uniform dispersion of the CuO.
[0107] 2.2) 14.65 g of TiC₄ powder was added to the uniformly dispersed CuO suspension. The mixed suspension was electromagnetically stirred at 200 rpm and 10 kHz for 20 min, ball-milled for 240 min, and then dried using a vacuum rotary evaporator. The rotary evaporator was placed in a thermostatic water bath at 30°C for 2 h and then dried at 100 rpm to obtain a CuO / TiC₄ composite powder.
[0108] (3) Rapid hot pressing sintering
[0109] 3.1) 15 g of CuO / TC4 composite powder was placed into a 20 mm Φ cylindrical graphite mold. The mold was then placed in a hydraulic press with a preload of 20 MPa and maintained for 60 min. The powder mixture was then compacted.
[0110] 3.2) The compacted green body was placed in a rapid hot pressing furnace with an initial vacuum of ≤5 Pa and an initial heating rate of 10°C / min. When the temperature reached 300°C, the heating rate was adjusted to 50°C / min. When the temperature reached 600°C, the green body was held at that temperature for 20 minutes and then cooled in the furnace to complete the rapid hot pressing sintering of the green body. A sintered CuO / TC4 green body was obtained.
[0111] (4) Thermal deformation during variable speed rolling
[0112] 4.1) The CuO / TC4 sintered body was first subjected to thermal deformation treatment using a low-speed rolling process. The starting rolling temperature was 800°C, and the circumferential speed of the upper and lower rollers was controlled to be equal and the rotation speed was 100 r / min. The deformation amount per pass was 5%, and the total deformation amount was 20%. The re-melting temperature between passes was 800°C, and the re-melting holding time between passes was 8 minutes.
[0113] 4.2) The pre-deformed blank was then subjected to thermal deformation treatment by high-speed rolling, with an initial rolling temperature of 800°C and a peripheral speed of 500 r / min. The deformation amount per pass was 10%, and the total deformation amount was 30%. The inter-pass re-melting temperature was 800°C, and the inter-pass re-melting holding time was 8 min, to obtain the final processed sample.
[0114] Comparative Example 4
[0115] A method for preparing high-strength and toughness titanium-based composite materials by solid-phase reaction sintering, the specific steps are as follows:
[0116] (1) Weigh 15 g of pure TC4 and add it to 100 mL of ethanol solution. After electromagnetic stirring at a rate of 200 r / min and a frequency of 10 kHz for 20 min, ball mill for 240 min, and then dry it using a vacuum rotary evaporator. The rotary evaporation bottle is placed in a constant temperature water bath at a temperature of 30°C for 2 h and rotary evaporated at a rotation speed of 100 r / min to obtain the ball-milled titanium matrix powder.
[0117] (2) The powder after ball milling and drying in (1) is loaded into a Φ20mm cylindrical graphite mold, and the graphite mold is then placed in a hydraulic press, with a pre-pressure of 20MPa and pressure maintained for 60min; then the powder mixture is pressed and formed; the pressed green compact is placed in a rapid hot pressing furnace, with an initial vacuum degree of ≤5Pa and an initial heating rate of 10°C / min. When the temperature rises to 300°C, the heating rate is adjusted to 50°C / min, and when the temperature rises to 600°C, the temperature is maintained for 20min, and then cooled with the furnace to complete the rapid hot pressing sintering of the green compact to obtain a sintered TC4 green body;
[0118] (3) First, the pure titanium sintered blank is subjected to thermal deformation treatment by low-temperature and low-speed rolling process, the starting rolling temperature is 800℃, the circumferential speed of the upper and lower rollers is controlled to be equal and the rotation speed is 100r / min; the deformation amount of each pass is 5%, and the total deformation amount is 20%; the furnace temperature between passes is 800℃, and the furnace holding time between passes is 8min; secondly, the pre-deformed blank is subjected to thermal deformation treatment by high-speed rolling, the starting rolling temperature is 800℃; the circumferential speed of the high-speed roller is 500r / min; the deformation amount of each pass is 10%, and the total deformation amount is 30%; the furnace temperature between passes is 800℃, and the furnace holding time between passes is 8min, and the final processed sample is obtained.
[0119] In summary, the composite materials obtained by different experimental methods in several examples respectively use the solid-phase sintering method by adding copper oxide to disperse the nanoscale reinforcement material into the matrix grains, thereby realizing intragranular reinforcement of the matrix through dislocation accumulation, and the regulation of the precipitated phase is realized through multi-pass variable-speed hot processing, making the organization more uniform, reducing the segregation of the sintered parts, and eliminating the rough and uneven microstructure, thereby obtaining a high-strength and high-toughness titanium-based composite material.
[0120] Table 1 Comparison of room temperature properties of titanium-based composite materials prepared in Examples and Comparative Examples
[0121]
[0122] The present invention provides a method for preparing a novel high-strength and tough titanium-based composite material. The preparation method is simple, has a short experimental cycle, and is economical and affordable. The resulting composite material has high strength and good tensile properties. A large amount of heat is released through a solid-phase reaction, making the reaction more intense, faster, and sintering in a shorter time, and at a lower temperature. Combined with thermal processing deformation, the resulting eutectoid Ti2Cu phase exhibits a unique micronetwork distribution at the grain boundaries and uniform distribution within the crystals. This is primarily due to the nano-Ti2Cu phase and its ability to effectively suppress dislocation motion, precipitation strengthening, and dislocation strengthening. This method provides technical guidance for the development of high-performance titanium-based composite materials.
[0123] In summary, the above embodiments are only preferred embodiments of the present invention, and are not intended to be exhaustive. They are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention shall be included in the scope of protection of the present invention.
Claims
1. A method for preparing a high-strength and tough titanium-based composite material by solid phase reaction sintering, characterized in that: The method steps are as follows: (1) copper acetate (Cu(CH3COO)2·H2O) and sodium hydroxide (NaOH) are dissolved in deionized water respectively, sodium hydroxide is added dropwise into the copper acetate, and the mixed solution is subjected to magnetic stirring, heating, washing, suction filtration, and drying to prepare nano copper oxide (CuO); (2) uniformly dispersing CuO in an ethanol solution by ultrasonication to obtain a CuO suspension, then adding a titanium matrix powder to the CuO suspension, stirring and mixing, ball milling and drying to obtain a CuO / Ti-based composite powder; (3) sintering the CuO / Ti composite powder: molding the dried CuO / Ti composite powder into a cylindrical green compact, moving the green compact into a sintering furnace for sintering, and obtaining a consolidated sintered green body; (4) The sintered green body is subjected to thermal deformation treatment by rolling thermal deformation process. The different distribution states of nano-Ti2Cu and titanium matrix in the matrix are controlled by adjusting the thermal deformation parameters, and finally the grain boundary micro-network distribution and intracrystalline distribution of the reinforcement nano-Ti2Cu are achieved to obtain a high-strength and toughness titanium-based composite material.
2. The method for preparing a high-strength and tough titanium-based composite material by solid phase reaction sintering according to claim 1, characterized in that: The specific steps of preparing nano copper oxide in step (1) are as follows: Dissolve (Cu(CH3COO)2·H2O) and NaOH in deionized water respectively and disperse them ultrasonically to obtain a blue suspension and a transparent solution. Then, add NaOH solution drop by drop into the (Cu(CH3COO)2·H2O) suspension until a large amount of dark blue precipitate is produced in the suspension. Heat and stir the obtained suspension in a 70-80°C magnetic stirring water bath until the suspension completely turns black. Keep warm and stir magnetically for 30 minutes. After the reaction is completed, wash the suspension with deionized water to obtain a colorless and neutral filtrate. Vacuum filter the suspension, and dry the obtained CuO under vacuum conditions at 60-70°C for 4-6 hours to obtain the prepared black powder nano-CuO.
3. The method for preparing a high-strength and tough titanium-based composite material by solid phase reaction sintering according to claim 1, characterized in that: The stirring in step (2) is carried out by electromagnetic stirring at a stirring rate of 200-800 r / min for 10-20 min and a frequency of 10-60 KHz.
4. The method for preparing a high-strength and tough titanium-based composite material by solid phase reaction sintering according to claim 1, characterized in that: The drying in step (2) is performed by using a vacuum rotary evaporator to remove the alcohol solution to obtain a powder mixture, wherein the rotary evaporating flask is placed in a constant temperature water bath at a temperature of 30-60° C. for 1-2 hours, and the flask rotates at a speed of 10-100 r / min.
5. The method for preparing high-strength and toughness titanium-based composite materials by solid phase reaction sintering according to claim 1, characterized in that: The specific steps of the green compaction in step (3) are as follows: loading the CuO / Ti composite powder into a graphite mold, placing the graphite mold containing the powder mixture into a hydraulic press, setting a pre-pressure of 0-20 MPa, and maintaining the pressure for 0-60 minutes; and completing the pressing and forming of the powder mixture.
6. The method for preparing high-strength and toughness titanium-based composite materials by solid phase reaction sintering according to claim 1, characterized in that: The specific sintering steps of step (3) are as follows: placing the pressed green sheet into a rapid hot pressing sintering furnace, and the preset sintering program is that the initial vacuum degree is ≤5Pa, the initial heating rate is set to 10-50℃ / min, and when the temperature rises to 300-500℃, the heating rate is adjusted to 50-100℃ / min, and when the temperature rises to 600-950℃, it is kept warm for 5-20min, and then cooled with the furnace to complete the rapid hot pressing sintering of the green sheet to obtain a dense green sheet.
7. The method for preparing high-strength and toughness titanium-based composite materials by solid phase reaction sintering according to claim 1, characterized in that: The thermal deformation treatment in step (4) adopts a multi-pass variable speed rolling thermal deformation process, firstly adopting a low speed rolling process to perform thermal deformation treatment on the sintered blank, and then adopting a high speed rolling process to perform thermal deformation treatment on the pre-deformed blank.
8. The method for preparing high-strength and high-toughness titanium-based composite materials by solid phase reaction sintering according to claim 7, characterized in that: The step (4) of low-speed rolling is performed as follows: the starting rolling temperature is 800-1000°C, the circumferential speeds of the upper and lower rollers are controlled to be equal, and the rotation speed is 100-600r / s; the deformation amount of each pass is 3-40%, and the total deformation amount is 10-80%; the re-melting temperature between passes is 800-1000°C, and the re-melting insulation time between passes is 2-8min.
9. A method for preparing a high-strength and tough titanium-based composite material by solid phase reaction sintering according to claim 7 or 8, characterized in that: The step (4) high-speed rolling is performed according to the following steps: the starting rolling temperature is 800-1000°C; the rotation speed is 500-1000r / s; the deformation amount of each pass is 3-40%, and the total deformation amount is 10-80%; the re-melting temperature between passes is 800-1000°C, and the re-melting insulation time between passes is 2-8min, and finally a titanium-based composite material with Ti2Cu with grain boundary micro-network distribution and intracrystalline nano-Ti2Cu coupling reinforcement is prepared.
10. A method for preparing a high-strength and tough titanium-based composite material by solid phase reaction sintering according to any one of claims 1 to 9: in the step (1), the molar ratio of copper acetate to sodium hydroxide is 3:5, and the concentration of copper acetate in the aqueous solution is 3-15 mg / mL.